DAMPAK PEMBERDAYAAN DAN KOMUNIKASI INTERPERSONAL DALAM MENINGKATKAN ORGANIZATIOAN CITYZENSHIP BEHAVIOR KARYAWAN GENERASI Y - Susi Adiawaty; Maria Angellina Daso (POLITEKNIK LP3I JAKARTA, 2023)
This research aims to see the influence of empowerment and interpersonal communication on improving organizational citizenship behavior. The influence seen is the partial influence and the simultaneous influence between the dependent variable and the independent variable. The research was conducted on 92 WJU Generation Y employees. The research is quantitative using two analysis methods, namely the descriptive method and the data analysis method using SMART PLS. To see the influence of the dependent variable on the independent variable, the t test and F test were used. The research results show that empowerment and interpersonal communication can influence the increase in employee organizational citizenship behavior both partially and simultaneously. Between these two influences, it is known that the influence of empowerment is higher than the influence of interpersonal communication. The aspects of interpersonal communication that need to be improved so that increasing organizational citizenship behavior has a stronger impact are the alturism aspect and the sportsmanship aspect. Keywords: Empowerment, Interpersonal Communication, Organizational citizenship behavior